Leadership, Artificial Intelligence and the Need to Redefine Future Skills Development - Moldenhauer, Lize; Londt, Cindy (Journal of Leadership, Accountability and Ethics, 2019)
The evolution of artificial intelligence has resulted in the need to establish alignment of artificial intelligence to various avenues of life and that of Leadership in an Artificial Intelligence based economy. Challenges associated to the independence of artificial intelligence, in addition to possible autonomy, are the focus of thought. As part of this paper, the focus is on the links between artificial intelligence and leadership, and its relationship, if any. A case study has been done on an organisation that has developed a model for the training of staff towards the AI model of leadership.